2011
DOI: 10.1038/aja.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

The role of varicocele sclerotherapy in men with severe oligo-astheno-teratozoospermia

Abstract: The aim of this study was to verify the role of antegrade scrotal sclerotherapy for the treatment of varicoceles in infertile men with severe oligo-astheno-teratozoospermia (OAT). The 59 patients with severe OAT in this study underwent antegrade scrotal sclerotherapy for the treatment of varicoceles. The outcome was assessed in terms of improvement in semen parameters and spontaneous conception rate. Semen parameters and reproductive hormones were evaluated before antegrade sclerotherapy (AS) and 6 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Inhibin B is an important factor in testicular hormonal function. In men with severe oligoasthenoteratozoospermia, treatment of varicocele was associated with a significant increase in inhibin B levels and a significant decrease in FSH levels [ 8 ]. Some researchers have noted a significant improvement in serum inhibin B level after varicocelectomy and have concluded that combining this endocrine marker with a spermogram could be an effective guide to the effect of varicocelectomy on spermatogenesis [ 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibin B is an important factor in testicular hormonal function. In men with severe oligoasthenoteratozoospermia, treatment of varicocele was associated with a significant increase in inhibin B levels and a significant decrease in FSH levels [ 8 ]. Some researchers have noted a significant improvement in serum inhibin B level after varicocelectomy and have concluded that combining this endocrine marker with a spermogram could be an effective guide to the effect of varicocelectomy on spermatogenesis [ 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite heterogeneity in patient characteristics, diagnostic criteria, treatment methods and treatment outcomes, most researchers have found that varicocele repair is associated with a significant improvement in the sperm concentration (in 15 out of 22 studies) and progressive motility (in 12 out of 17 studies) [ 4 ]. Varicocele repair's effect on sperm morphology is less clear [ 6 8 ] and it has been suggested that significant morphological changes in germ cells can only be observed over long follow-up periods [ 7 ]. Menkveld et al [ 9 ] showed that the measurement or evaluation of sperm morphology remains therefore a very important tool in the diagnosis of a male’s fertility potential and in the clinical decision making for the treatment of patients with infertility problems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several published reports confirmed the positive impact of varicocelectomy on improvement of seminal parameters (Feber & Kass, 2008; Ghanem, Safan, Ghanem, & Dohle, 2011; Nevoux, Mitchell, Chevallier, Rigot, & Marcelli, 2011). However, to our knowledge, few reports have investigated the effects of platelet volume parameters on infertility outcome in varicocele (Mahdavi‐Zafarghandi et al, 2014; Polat et al, 2015; Polat, Gulpimar, Sarica, & Benlioglu, 2017; Pyoa & Cho, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…Although outcome of varicocele correction has been linked to the significant improvements of semen parameters in 60%–80% of men after varicocelectomy (Feber & Kass, 2008; Ghanem et al, 2011; Nevoux et al, 2011), a little is known about the value of preoperative and postoperative haematological markers for follow‐up varicocele cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation